Integrating Project-Based Learning within Outcome-Based Education Framework: A Literature Review on Polytechnic English Language Education - Lestari, Pratiwi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2025)
This literature review discusses how integrating Project-Based Learning (PjBL) within the Outcome-Based Education (OBE) framework can enhance English teaching in polytechnic education. The review highlights that this approach increases student engagement, improves their ability to use English in real life situations, and supports the development of 21st-century skills such as teamwork and critical thinking. PjBL aligns with OBE’s focus on clear and measurable learning outcomes that meet vocational and industry needs through authentic tasks like presentations and reports. However, successful implementation requires overcoming challenges such as limited resources, insufficient teacher training, and complex assessment procedures. The paper offers suggestions including improved curriculum design, professional development for educators, enhanced learning tools, and supportive policies. With these supports, integrating PjBL into OBE can make English learning more relevant and effective for vocational students.